2018
DOI: 10.12820/rbafs.23e0010
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior as a predictor of functional disability in older adults

Abstract: The aim of this study was to identify the amount of time spent in sedentary behavior that may be critically related to functional disability in older adults. A cross-sectional study was conducted with a random sample of 624 older adults (65.1% women) aged 60 to 96 years. Perceived limitations in instrumental activities of daily living were used as indication of functional disability. Time spent in sedentary behavior was assessed using the International Physical Activity Questionnaire (IPAQ). The prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
(22 reference statements)
0
3
0
6
Order By: Relevance
“…Sedentary behavior, as well as frailty, had a negative effect on functional capacity for the instrumental activities, in which the longer the time in a seated position, the worse the performance in daily tasks, as identified in national ( 39 ) and international studies ( 6 ) . These results are relevant, considering that, in systematic reviews, it was identified that people aged 60 years old or older spend a mean of nine hours a day in sedentary behavior ( 40 ) and, as a consequence, present worse health conditions, which represent a risk not only to life, but also to the preservation of the autonomy and independence of the aging population ( 41 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedentary behavior, as well as frailty, had a negative effect on functional capacity for the instrumental activities, in which the longer the time in a seated position, the worse the performance in daily tasks, as identified in national ( 39 ) and international studies ( 6 ) . These results are relevant, considering that, in systematic reviews, it was identified that people aged 60 years old or older spend a mean of nine hours a day in sedentary behavior ( 40 ) and, as a consequence, present worse health conditions, which represent a risk not only to life, but also to the preservation of the autonomy and independence of the aging population ( 41 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that older adults with longer time spent in sedentary behaviors perform worse in the components of physical fitness ( 49 ) , which are decisive for activities related to self-care ( 50 ) . In addition, sedentary behavior has been shown to be associated with worse outcomes for inflammatory biomarkers ( 39 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, older adults who were dependent in basic activities of daily living had higher frequency of exposure to sedentary behavior, compared to older adults who were independent. There is evidence that prolonged periods of sitting are associated with disability in activities of daily living in older adults 18 . The current study also demonstrated that negative perceptions of health increased significantly from the lower to the upper quartile of sedentary behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, características ambientais de vizinhança favoráveis estão associados à menor tempo gasto (PITANGA et al, 2018), como também espaços estruturados e seguros para a prática de atividade física no lazer (ARINS et al, 2018). O tempo gasto com comportamento sedentário é preocupante, pois está relacionado diretamente com reduções na capacidade de realizar atividades básicas da vida diária de maneira independente (VIRTUOSO JÚNIOR et al, 2018;BERTOLINI et al, 2016), excesso de peso (JESUS; ROCHA, 2018), perda da massa muscular (LASZLO, 2016) e vulnerabilidade a quedas e fraturas (SANTOS et al, 2015).…”
Section: R E S U L T a D O S E D I S C U S S ã Ounclassified